2004
DOI: 10.1042/cs20030315
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Mediterranean-inspired diet on blood lipids, vascular function and oxidative stress in healthy subjects

Abstract: Mediterranean-inspired diets have been shown to decrease cholesterol levels in patients with hypercholesterolaemia, who frequently exhibit endothelial dysfunction. The aims of the present study are to improve endothelial function by dietary intervention in healthy subjects with lipid levels representative of a Western population. Twenty-two healthy subjects (mean total cholesterol, 5.6 mmol/l) were given a Mediterranean-inspired diet rich in omega-3 fatty acids and sterol esters, but low in saturated fat, or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
2
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 28 publications
4
75
2
3
Order By: Relevance
“…There are short-term interventional studies analyzing the effects of the Mediterranean diet on circulating oxidative stress biomarkers, but not measuring the TAC (Hagfors et al, 2003;Ambring et al, 2004;Zulet et al, 2008;Puchau et al, 2009). Moreover, this study goes further and analyzes the influence of this antioxidant capacity of the three nutritional interventions on adiposity indexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are short-term interventional studies analyzing the effects of the Mediterranean diet on circulating oxidative stress biomarkers, but not measuring the TAC (Hagfors et al, 2003;Ambring et al, 2004;Zulet et al, 2008;Puchau et al, 2009). Moreover, this study goes further and analyzes the influence of this antioxidant capacity of the three nutritional interventions on adiposity indexes.…”
Section: Discussionmentioning
confidence: 99%
“…There are also short-term interventional studies analyzing the Mediterranean diet and its potential association with other oxidative stress biomarkers (Hagfors et al, 2003;Ambring et al, 2004), but there are not long-term interventional studies about this issue. Our study is a 3-year randomized trial that supports the idea that a greater adherence to Mediterranean diet is associated with higher plasma antioxidant capacity (Pitsavos et al, 2005;Dai et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that glucose is simply more sensitive to dietary change in general than is insulin. In a wide range of intervention studies testing the effects of a variety of dietary interventions (including low-fat diets, low-glycemic index diets, the DASH diet, Mediterranean diet, high-fiber diets and diets that substitute mono-unsaturated fat in place of saturated fat), it was frequently the case that if the investigators observed any changes, they observed decreases in glucose concentration but no change in insulin concentration (Fukagawa et al, 1990;Landin et al, 1992;Straznicky et al, 1999;Bisschop et al, 2001;Bouche et al, 2002;Miller et al, 2002;Hall et al, 2003;Juntunen et al, 2003;Kaaks et al, 2003;Ambring et al, 2004;Heald et al, 2004;Sloth et al, 2004). Our results are consistent with these findings.…”
Section: Effects Of a Dietary Intervention On Insulin Glucose Igf-imentioning
confidence: 99%
“…Results from 12 dietary intervention studies in normal-weight, healthy individuals were somewhat mixed with many, but not all, showing modest reductions in fasting glucose concentration after the intervention but little change in insulin. These studies, however, were generally small (only one study enrolled as many as 100 subjects, with over half enrolling fewer than 25), used interventions of brief duration (interventions were longer than 12 weeks in only two studies and never longer than 6 months) and frequently involved significant weight change (Fukagawa et al, 1990;Landin et al, 1992;Straznicky et al, 1999;Bisschop et al, 2001;Bouche et al, 2002;Miller et al, 2002;Hall et al, 2003;Juntunen et al, 2003;Kaaks et al, 2003;Ambring et al, 2004;Heald et al, 2004;Sloth et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The observed lowering of plasma cholesterol was reported to indicate a potential 9% reduction in cardiovascular risk in the low-fat diet group compared with 15% in the Mediterranean diet group (125) . Other intervention studies have also demonstrated a beneficial lipid-altering effect (126,127) , including HDL-raising effects (48,115) . Mediterranean diet and body weight and blood pressure.…”
Section: Mechanism Of Actionmentioning
confidence: 99%